Patient Factors Associated with Recurrent Herniation and Revision Surgery following Lumbar Microdiscectomy - Ryan Hoang; Junho Song; Justin Tiao; Alex Ngan; Timothy Hoang; John J. Corvi; Nikan K. Namiri; Saad Chaudhary; Samuel K. Cho; Andrew C. Hecht; David Essig; Sohrab Virk; et al. (Spine Surgery and Related Research)
Introduction: Lumbar microdiscectomy is a commonly conducted surgical procedure for treating symptomatic lumbar disc herniations. Recurrence of herniation is a common cause of poor outcomes and the need for revision surgery, which occurs in as many as 21% of patients following primary discectomy. Identifying factors that are associated with the recurrence of herniation may be valuable for risk stratification and patient counseling. This study aimed to explore the relationship between various patient demographic variables and comorbidities and rates of reoperation after primary lumbar microdiscectomy. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried for patients who were undergoing single-level primary lumbar microdiscectomy between 2016 and 2022. Eligibility for inclusion was determined by age >18 years and current procedural terminology codes 63030 and 63042. Patients with preoperative sepsis or cancer were excluded. Patient demographics, including age, race, ethnicity, and body mass index (BMI), and various comorbidities were compared between cohorts. To determine factors independently associated with the need for revision microdiscectomy, multivariable Poisson regressions were utilized. Results: In this study, a total of 65,121 primary discectomy patients were included, with a separate cohort of 6,971 patients undergoing revision discectomy. In comparison with primary patients, the revision cohort was older and had higher proportions of female and non-Hispanic White patients (all c0.001). The odds ratio for revision discectomy was greater in patients aged 65 years (1.577, 95% CI [1.480, 1.680]) than in those aged <45 years (p>0.001). The odds ratio for revision was lower in Black (0.821, 95% CI [0.738, 0.914]) and Hispanic patients (0.819, 95% CI [0.738, 0.909]) when compared with non-Hispanic White patients (p<0.001). Obese patients with BMI 35 (1.193, 95% CI [1.103, 1.290]) were at greater risk of revision than those with BMI <25 (p<0.001). Diabetes (1.326, 95% CI [1.242, 1.416], p<0.001), functional dependence (1.411, 95% CI [1.183, 1.683], p<0.001), chronic obstructive pulmonary disorder (1.315, 95% CI [1.137, 1.512], p<0.001), hypertension (1.398, 95% CI [1.330, 1.470], p<0.001), and smoking (1.082, 95% CI [1.018, 1.151], p=0.012) were associated with greater risk of revision. Poisson log-linear regression demonstrated sex (χ2=19.9, p<0.001), race (χ2=39.5, p<0.001), diabetes (χ2=10.1, p=0.001), smoking (χ2=18.5, p<0.001), hypertension (χ2=16.4, p<0.001), age (χ2=102.4, p<0.001), and BMI (χ2=4.7, p=0.029) as significant predictors of revision, with steroid use (χ2=3.5, p=0.061) and functional status (χ2=3.7, p=0.055) approaching significance. Conclusions: Patient demographics, comorbidities, and rehabilitative status may be significantly associated with rates of reherniation and revision surgery following lumbar microdiscectomy. We found that the significant predictors of revision surgery are functional dependence, advanced age, male sex, White race, obesity, diabetes, smoking, and hypertension. Early identification and attendance to the modifiable risk factors will aid patient guidance and outcomes following primary lumbar microdiscectomy.